2020
DOI: 10.3390/cryst10040337
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling of Residual Stress in Laser Powder Bed Fusion Considering Part’s Boundary Condition

Abstract: Rapid and accurate prediction of residual stress in metal additive manufacturing processes is of great importance to guarantee the quality of the fabricated part to be used in a mission-critical application in the aerospace, automotive, and medical industries. Experimentations and numerical modeling of residual stress however are valuable but expensive and time-consuming. Thus, a fully coupled thermomechanical analytical model is proposed to predict residual stress of the additively manufactured parts rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Moreover, the molecular dynamic method was used to investigate the effects of crystalline form, temperature, and grain orientation of columnar grains on the mechanical properties of SLM aluminum, which showed that reasonable control of the grain orientation can improve the tensile strength of the AM materials [70]. The Green's function of stresses was used to present the thermal stresses and the Johnson-Cook flow stress model was used to predict the yield surface of the part under repeated heating and cooling [71]. A crystal plasticity finite element model was proposed to simulate the stress-strain response and fatigue crack initiation life of AM IN718 with different microstructures under tensile loadings [72].…”
Section: Experiments and Numerical Simulationsmentioning
confidence: 99%
“…Moreover, the molecular dynamic method was used to investigate the effects of crystalline form, temperature, and grain orientation of columnar grains on the mechanical properties of SLM aluminum, which showed that reasonable control of the grain orientation can improve the tensile strength of the AM materials [70]. The Green's function of stresses was used to present the thermal stresses and the Johnson-Cook flow stress model was used to predict the yield surface of the part under repeated heating and cooling [71]. A crystal plasticity finite element model was proposed to simulate the stress-strain response and fatigue crack initiation life of AM IN718 with different microstructures under tensile loadings [72].…”
Section: Experiments and Numerical Simulationsmentioning
confidence: 99%
“…For FLM ("Fused Layer Modelling") as well as in laser-based LBM ("laser beam melting") and EBM ("electron beam melting") processes, samples with different geometries are used in product/process development. The use of a rectangular parallelepiped [9], a tensile test geometry [10,11], a solid cylindrical rod [12], and the combined use of a cube and a parallelepiped [13] are known for the evaluation of AMprocesses. In the following, requirements and criteria are described which are placed on a sample for the assessment of the additive-subtractive process chain using the example of the laser metal wire deposition (LMWD) process.…”
Section: Test Sample Geometrymentioning
confidence: 99%
“…If the stress passes the yield strength, upon unloading (cooling in this situation) some amount of stress remains in the body, which is known as RS. The RS is inherent in all the AM parts and can be reduced or eliminated with proper control and optimization of process parameters or post-processing techniques such as pitting, and heat treatment since it has an elastic nature [34,35].…”
Section: Mechanical Analysismentioning
confidence: 99%